Chitin nanofibers as versatile bio-templates of zeolitic imidazolate frameworks for N-doped hierarchically porous carbon electrodes for supercapacitor. (1st January 2021) - Shang, Zhen; An, Xingye; Liu, Liqin; Yang, Jian; Zhang, Wei; Dai, Hongqi; Cao, Haibing; Xu, Qingliang; Liu, Hongbin; Ni, Yonghao
Graphical abstract: Highlights: Crab shell derived ChNF are isolated via integrated HCl hydrolysis. ChNF as versatile bio-templates for ZIF-8 to form ChNF@ZIF-8 nanocomposites. ChNF and ZIF-8 act as efficient N-doping sources for fabricating N-HPC. 3D interconnected ChNF@ZIF-8 structures facilitate the increased N-HPC porosity. N-HPC electrodes assembled supercapacitors have enhanced capacitive performance. Abstract: Biobased N-doped hierarchically porous carbon (N-HPC) electrodes were successfully prepared by utilizing marine crustacean derivatives and chitin nanofibers (ChNF), as versatile bio-templates of zeolitic imidazolate frameworks (ZIF-8) to form ChNF@ZIF-8 nanocomposites, followed by a subsequent carbonization process. The ZIF-8 nanoparticles were in situ synthesized on ChNF surfaces to avoid fragmentation for fabricating hierarchically porous carbon structure (N-HPC), which is efficiently doped with rich nitrogen content that originates in ChNF and ZIF-8. The results show that N-HPC electrodes demonstrate improved electrochemical performance and the constructed symmetric supercapacitor assembled with N-HPC exhibits enhanced capacitive performance of specific capacity (128.5 F·g −1 at 0.2 A·g −1 ) and excellent electrochemical stability even after 5000 cycles. This facile and effective preparation method of N-HPC electrodes derived from marine crustacean nanomaterials will have great potential in the construction of next-generation electrochemical energy-storage devices with excellent capacitance performance.